2020
DOI: 10.3390/app10155126
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Anaerobic Co-Digestion of Lignocellulosic Biomass (Sugar Beet By-Products) and Animal Manure in Long-Term Semi-Continuous Assays

Abstract: Biogas production through anaerobic digestion has proven to be one of the most important pillars of the transition into the circular economy concept, a sustainable approach for biorefinery. This work aims to extend and improve knowledge in the anaerobic co-digestion of complementary substrates, given insights into wastes biodegradability and the influence of manure composition on the anaerobic process stability. Anaerobic co-digestion of sugar beet by-products with two kinds of animal manure (pig and cow) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
(76 reference statements)
3
14
0
Order By: Relevance
“…On the other hand, it is interesting to note that the inhibitory effect caused by OMW seems to have been compensated through the balance found in the complementarity with acidity and nutrients, therefore the mixture 70P + 30O provided better results in the removal of solids and COD (Table 5) than PE without mixtures. The mitigating inhibitory effects were also reported when complementary substrates were anaerobically digested [46]. Concerning polyphenols, an increase in concentration was observed as the OMW volume rose in the substrate, as was expected to occur (Table 6).…”
Section: Anaerobic Digestion Of Pe and Omw Mixturesupporting
confidence: 56%
“…On the other hand, it is interesting to note that the inhibitory effect caused by OMW seems to have been compensated through the balance found in the complementarity with acidity and nutrients, therefore the mixture 70P + 30O provided better results in the removal of solids and COD (Table 5) than PE without mixtures. The mitigating inhibitory effects were also reported when complementary substrates were anaerobically digested [46]. Concerning polyphenols, an increase in concentration was observed as the OMW volume rose in the substrate, as was expected to occur (Table 6).…”
Section: Anaerobic Digestion Of Pe and Omw Mixturesupporting
confidence: 56%
“…In this case, the OLR increased significantly (46%) in comparison with the other experiments. These results indicate that co-digestion improves methane production, due to the synergism between co-substrates, which increase the efficiency in terms of methane yield per unit of organic matter removed (Aboudi et al, 2020). This synergism was higher when black oat was used as co-substrate which allowed for working at a higher OLR.…”
Section: Semi-continuous Experimentsmentioning
confidence: 75%
“…The assumption considered additive effects in methane production disregarding synergistic effects, which would lead to better results due to the higher gas obtained and lower volume of digestate needing final disposal. Different authors have widely reported synergistic effects when evaluating mixtures of manures and carbon-rich content substrates [87][88][89][90]. Therefore, the remaining amount of solids in the digested slurry should not be significantly affected.…”
Section: Scenariomentioning
confidence: 99%